2017
DOI: 10.18632/oncotarget.17638
|View full text |Cite|
|
Sign up to set email alerts
|

Bushen-Yizhi formula ameliorates cognitive dysfunction through SIRT1/ER stress pathway in SAMP8 mice

Abstract: The Chinese formula Bushen-Yizhi (BSYZ) has been reported to ameliorate cognitive dysfunction. However the mechanism is still unclear. In this study, we employ an aging model, SAMP8 mice, to explore whether BSYZ could protect dementia through SIRT1/endoplasmic reticulum (ER) stress pathway. Morris water maze and the fearing condition test results show that oral administration of BSYZ (1.46 g/kg/d, 2.92 g/kg/d and 5.84 g/kg/d) and donepezil (3 mg/kg/d) shorten the escape latency, increase the crossing times of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 70 publications
0
16
0
Order By: Relevance
“…Aging is the main cause to lead the occurrence of AD and PD. BSYZ is usually used in the treatment of dementia and aging-related memory deficiency in China [ 23 ]. However, it remains unknown whether BSYZ is also effective for PD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aging is the main cause to lead the occurrence of AD and PD. BSYZ is usually used in the treatment of dementia and aging-related memory deficiency in China [ 23 ]. However, it remains unknown whether BSYZ is also effective for PD.…”
Section: Discussionmentioning
confidence: 99%
“…BSYZ, a traditional Chinese medicine, is composed of common Cnidium fruit, tree peony bark, ginseng root, Radix Polygoni Multiflori Preparata, Barbary wolfberry fruit, and Fructus Ligustri Lucidi. Our previous studies have confirmed that BSYZ has extensive neuroprotective effects such as antisenesce, antiapoptosis, and alleviation of oxidative stress in various Alzheimer's disease (AD) animal models [ 23 26 ]. Our recent investigation further demonstrated BSYZ is effective in reducing age-related neurodegenerative disorders via antineuroinflammation [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Based on these studies, silibinin potentially acts on multiple targets to inhibit AD pathologies. However, the effects of In the present study, learning and memory deficits were assessed using the Y-maze test, novel object recognition test and Morris water maze test, which are widely used methods to investigate the behaviors of mice [17][18][19][20]. The contents of soluble and insoluble Aβ and Aβ plaques are increased in 6-month-old APP/PS1 mice, comparable to patients with AD [21,22].…”
Section: Discussionmentioning
confidence: 86%
“…Therefore, modulation of neurotransmitter levels has been suggested as a therapeutic target, as evidenced by the use of serotonin reuptake inhibitors (SSRIs) and acetylcholinesterase inhibitors (AChEIs) for the treatment of cognitive impairment ( Recanatini and Valenti, 2004 ). Degeneration of catecholaminergic neurons (including dopaminergic and noradrenergic) seriously worsens in SAMP8 mice from 8 months on ( Karasawa et al, 1997 ), and significant decrease of ACh level has been observed in 3-month old SAMP8 mice hippocampi and cortices ( Zhang et al, 2017 ). Enhanced synaptic plasticity in the cerebral cortex of STEE-fed mice could be explained by the significant upregulation of Mbp , a major myelin protein and essential for saltatory nerve conduction, and of Syt1 , an important regulator of synaptic vesicle transport ( Fields, 2015 ; Schupp et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%